Pseudomonas chlororaphis IRHB3 assemblies beneficial microbes and activates JA-mediated resistance to promote nutrient utilization and inhibit pathogen attack - Wei, Dengqin; Zhu, Dan; Zhang, Yunfeng; Yang, Zheng; Hu, Yu; Song, Chun; Yang, Wenyu; Chang, Xiaoli (Frontiers in Microbiology, 2024)
The rhizosphere microbiome is critical to plant health and resistance. PGPR are wellknown as the plant beneficial bacteria and generally regulates nutrient utilization as well as plant responses to environmental stimuli. In our previous work, one typical PGPR strain Pseudomonas chlororaphis IRHB3 isolated from soybean rhizosphere had positive impacts on soilborne disease suppression and growth promotion in the greenhouse, but its biocontrol mechanism and application in the field are not unclear.In current study, IRHB3 was introduced into field soil, and its effects on local rhizosphere microbiome, disease resistance as well as soybean growth were comprehensively analyzed through high-throughput sequencing, physiological and molecular methods. We found that IRHB3 significantly increased the richness in bacterial community but not structure in soybean rhizosphere. Functional bacteria related to phosphorus solubilization and nitrogen fixation like Geobacter, Geomonas, Candidatus Solibacter, Occallatibacter and Candidatus Koribacter, were recruited in rich abundance by IRHB3 to soybean rhizosphere as compared to those without IRHB3.In addition, IRHB3 supplement obviously maintained the homeostasis of rhizosphere microbiome that disturbed by F.oxysporum, resulting in a lower disease index of root rot when compared with F.oxysporum. Furthermore, JA-mediated induced resistance were rapidly activated by IRHB3 following PDF1.2 and LOX2 expression, and meanwhile, a set of nodulation genes GmENOD40b, GmNIN-2b and GmRIC1 were also considerably induced by IRHB3 to improve nitrogen fixation ability and promote soybean yield, even when plants were infected by F.oxysporum. Thus, IRHB3 trends to synergistically interact with local rhizosphere microbes to promote host growth and induce host resistance in the field .